PERAN FATHIMAH BINTI ABDUL WAHAB BUGIS DALAM SEJARAH PENDIDIKAN PEREMPUAN DI KALIMANTAN - ., Saifuddin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2009)
The story of the involving women in knowledge and Islamic education tradition is still the grey story. Nothing much to know about the subject. In Malay-Indonesia area, the struggle of women to have an acces in education, as some experts, started in the end of 19th century or in the beginning of 20th century, marked by the presence of women figures such as Kartini, Dewi Sartika, and rahman el-Yunusiah. This writing tries to submit another woman figure earlier than Kartini and her generations that is Fathimah binti Abdul Wahab Bugis.